2020
DOI: 10.15244/pjoes/108510
|View full text |Cite
|
Sign up to set email alerts
|

Functional Distribution of Bacterial Community under Different Land Use Patterns Based on FaProTax Function Prediction

Abstract: Soil microorganisms play an important role in biogeochemical cycling. The bacterial community functional community profiles across different land use types in the mountainous region of eastern Liaoning Province, China, such as natural secondary forest (Quercus mongolica (QM)), shrub wood (SW), coniferous planation (Larix gmelini (LG), and Pinus koraiensis (PK)), and agricultural land (Zea mays (ZM)) were evaluated using high-throughput sequencing of the bacterial 16S rDNA gene, and predicted based on the FaPro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 66 publications
5
34
0
Order By: Relevance
“…In this study, FaProTax software (Louca et al, 2016) was used to predict the ecological functions of the rhizosphere soil bacterial community during continuous cropping of Tibetan barley. The results indicated that chemoheterotrophy and aerobic chemoheterotrophy-related species were dominant in rhizosphere soil (Figure 3), which concurred with previous soil findings (Legrand et al, 2018;Che et al, 2019;Liang et al, 2020). We observed that the relative abundances of 16S rRNA gene sequences assigned to chemoheterotrophy and aerobic chemoheterotrophy increased significantly with continuous cropping duration ( Supplementary Figure S4).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, FaProTax software (Louca et al, 2016) was used to predict the ecological functions of the rhizosphere soil bacterial community during continuous cropping of Tibetan barley. The results indicated that chemoheterotrophy and aerobic chemoheterotrophy-related species were dominant in rhizosphere soil (Figure 3), which concurred with previous soil findings (Legrand et al, 2018;Che et al, 2019;Liang et al, 2020). We observed that the relative abundances of 16S rRNA gene sequences assigned to chemoheterotrophy and aerobic chemoheterotrophy increased significantly with continuous cropping duration ( Supplementary Figure S4).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have also been observed in soil with continuous cropping of cotton and tea (Li Y.C. et al, 2016;Wei and Yu, 2018;Xi et al, 2019;Liang et al, 2020). We inferred that changes in soil chemical properties could have contributed to the distinct variations in bacterial community structures, as soil chemical properties play critical roles in microbial community structures (Kuramae et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that the group capable of aromatic compound degradation was the main predictors of soil bacteria functional structure, then followed by the groups capable of aerobic chemoheterotrophy and chemoheterotrophy which were the predominant functional groups in soil ( Figures 1C , 2B ). These functional groups were related to the soil carbon cycle process ( Liang et al, 2020 ), and had a significant correlation with the corresponding soil enzyme activity ( Table 4 ), which indicated that changes in soil carbon pools may be the main factor driving soil bacterial functional structure ( O’donnell et al, 2001 ). Soil bacterial functional groups were closely related to the diversity of above-ground plants.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical calculations and analyses were performed using GraphPad Prism 6.0 software (GraphPad, La Jolla, CA, USA) and SPSS 19 software for Windows (IBM Corporation, Armonk, NY, USA). The bacterial functions of CTLs were predicted using FAPROTAX ( http://www.zoology.ubc.ca/louca/FAPROTAX/lib/php/index.php?section=Instructions ) (Liang et al, 2019 ). The trophic mode of the fungi was annotated using FUNGuild software ( http://www.stbates.org/guilds/app.php ) (Nguyen et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%